Technical Factors Affecting to Production of Dry-Salted Mudskipper (Pseudapocryptes Elongatus) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Mudskippers (Pseudapocryptes elongatus) are widely distributed in the brackish water, rivers, creeks and lagoons and are usually seen during low tide. Mudskipper (P. elongatus) is a potential species for coastal aquaculture and easy to farm in intensive or semi-intensive systems during rainy season in the Soc Trang province  (Vietnam). This species is considered as an alternative species to shrimp farming in rainy season. They are good sources of proteins, macro-nutrients, minerals and some vitamins. The mineral elemental levels and vitamins of this species is a function of the availability preferential accumulation. Aquaculture of P. elongatus in the Soc Trang province (Vietnam) has developed rapidly during the past decade due to relatively high demand and high market value. Drying stills continues to be the most widely used method for preservation of several foods including fish. Effectiveness of drying as a means of increasing the shelf life of fish is due to reducing growth of microorganism by reducing the availability of water.  Objective of this study focused on the effect of different aspects such as ethanol treatment to eliminate fishy ordor; addition of salt, sorbitol, as well as drying temperature that affected to to water activity, enterobacteriaceae load, and sensory score of dry-salted mudskipper. Shelf-life of the dried product was also evaluated during preservation. Results showed that 40% ethanol at ratio 25:75 for primary treatment; 2.5% of salt soaking; 1.25% of sorbitol addition; 48oC of drying were appropriate to maintain water activity (aw=0.65). By preserving under vacuum in PA bag, the dry-salted mudskipper still extended the product shelf-life for 12 months without any deterioration.Keywords: Mudskipper, Pseudapocryptes elongatus, Ethanol, Salt, Sorbitol, Drying, Enterobacteriaceae, Vacuum.